(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
تمت دراسة فعالية أنزيم الفوسفاتيز القاعدي في أمصال الدم لـ (30 ) عينة للرجال مصابين بسرطان العظام من مستشفى مدينة الطب /بغداد وقد لوحظ زيادة الفعالية الأنزيمية الكلية في الحالات المرضية حيث وصلت الى( 41.53 K.A.U./100ml ) مقارنة بالقيمة الطبيعية لفعالية أنزيم الفوسفاتيز القاعدي في مصل دم البالغين الأصحاء التي تكون ضمن المدى (3-13 K.A.U./100ml). تم دراسة تأثير المركبين 7-nitro isatindine nicotinoyl hydrazide , Isatindine nicotinoyl hydrazide على فعالية أنزيم الفوسفاتيز القاعدي في مصل الدم من خلال تحضير سلسلة من التراكيز (2*10-8, 2* 10-7, 2* 10-6,2* 10-5) M لكل من المركببين من المحلول القياسي (stock solution) بتركيز (M 10-4) لكل منهما وقد استخدم DMSO كمذيب ولغرض التخفيف، بعد أن تم قياس تأثير DMSO التثبيطي على أنزيم الفوسفاتيز القاعدي في مصل الدم والذي بلغ (2.76±0.5%)ومن خلال إجراء الفحوصات وجد أن المركبين يمكن اعتبارهما مثبطات جيدة بالتراكيز المستخدمة، حيث بلغ مدى النسبة المئوية للتثبيط (50-65%) وذلك باستخدام التركيزالأعلى للمثبطات (M 2*10-5) في مصل دم للمصابين . Abstract The level of Alkaline phosphatase was studied in the blood serum of (30) sample of men with bone cancer hospital in the town of Medicine / Baghdad has been observed to increase the overall effectiveness enzyme in patients with an average of (41.53 KAU/100ml) compared to the value of the effectiveness of the natural enzyme in theAlkaline phosphatase activity in sera of normal adults was in the ranges 3-13 K.A.U./100ml . The effect of compounds 7-nitro isatindine nicotinoyl hydrazide Isatindine nicotinoyl hydrazide. the effectiveness of enzyme (ALP) of with concentration(2*10-8, 2* 10-7, 2* 10-6,2* 10-5) of tow compounds in blood sera of stock solution concentration (M 10-4) and DMSO was used as solvent and diluents , The inhibitory effect of DMSO on Alkaline phosphatase in blood sera was(2.76±0.5%) the two compounds have a good inhibitory in this concentration the Ratio was (50-65) with the high concentration of inhibitor was (M2*10-5)in sera of patients.